وقف العوارض: استجابة السياسات للوباء والكوارث الطبيعية: WAQF AL AWARIDH: POLICY RESPONSE TO PANDEMIC AND GLOBAL DISASTER - Laeba, Muhammad; Mohamad, Nor Asiah; Ibrahim Negasi, Mohammad; Mahmoud Zaki, Hesham; Duramae, Ismail (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث تهدف هذه الورقة إلى بيان مفهوم وقف العوارض والحكم الشرعي له، باعتباره نوعاً من أنواع الوقف المؤقت. وذلك من خلال استعراض أهمية وقف العوارض والحاجة إليه في وقتنا الحاضر، وملاءمته لمقاصد الشريعة المعتبرة في حفظ النفس والمال من الكوارث الطبيعية، مثل الفيضانات والجوائح والنوازل، كجائحة كورونا (COVID-19) وغيرها. تكمن الإشكالية في أن كثيراً من الدول – ومنها ماليزيا وباكستان – تواجه هذه الكوارث الطبيعية بشكل متكرر، حيث أصبحت جزءاً من حياة المجتمع بسبب تغير المناخ. ومع ذلك، فإن موضوع وقف العوارض لم يأخذ حظاً كبيراً من الدراسة والبحث، ولا توجد دراسات تناولت هذا الموضوع بشكل مفصل (حسب اطلاع الباحثين). وتكمن أهمية وقف العوارض في كونه وسيلة لمساعدة المحتاجين والمتضررين بسبب هذه الكوارث والأمراض المعدية، والتخفيف من آثارها على المجتمع والأفراد. والأهم من ذلك، أنه يساعد على تخفيف العبء الحكومي في توفير التسهيلات والبنية التحتية جراء الأضرار التي تنشأ بسبب الكوارث الطبيعية. ويرى الباحثون أن هناك حاجة ماسة لتوعية المسلمين بهذا النوع من الوقف ونشر ثقافته، فهو يتيح لمعظم شرائح المجتمع المشاركة في الأوقاف بغض النظر عن حجم ثرواتهم وممتلكاتهم. إضافة إلى ذلك، فإن هذه الدراسة ستقدم آليات تطبيق وقف العوارض في ماليزيا. وقد اعتمدت هذه الدراسة على المنهج الاستقرائي والتحليلي. ABSTRACT The purpose of this paper is to explain the concept of Waqf Al-Awaridh (temporary suspension for emergencies) and its Sharia ruling as a form of temporary suspension (according to researchers). This is achieved by reviewing the importance of Waqf Al-Awaridh, its necessity in contemporary times, and its alignment with the objectives of Sharia in preserving life and wealth from natural disasters (such as volcanoes and floods), pandemics, and catastrophic events like the COVID-19 pandemic. The problem lies in the fact that many countries—including Malaysia, Turkey, and Pakistan—are increasingly facing these natural disasters, which have become a recurring part of societal life due to climate change. Despite this, the concept of Waqf Al-Awaridh has not received significant attention in academic research. To date, there is only one study on this topic, presented at the same annual conference in English, and subsequently published in a scientific journal at the end of last year (according to researchers). The importance of Waqf Al-Awaridh lies in its potential to assist those in need and those affected by disasters and infectious diseases, mitigating the impact on both society and individuals. Most importantly, it helps reduce the government's burden in providing facilities and infrastructure damaged by natural disasters. Researchers believe there is an urgent need to educate Muslims about this type of Waqf and to promote its understanding, as it allows all segments of society to participate in Waqf, regardless of their wealth or property. Additionally, this study proposes mechanisms for implementing Waqf Al-Awaridh in various countries. This study adopts an inductive and analytical approach to explore the concept and its applications.